2020
DOI: 10.1101/2020.05.22.110635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using GC content to compare recombination patterns on the sex chromosomes and autosomes of the guppy,Poecilia reticulata, and its close outgroup species

Abstract: Summary/AbstractGenetic and physical mapping of the guppy (P. reticulata) have shown that recombination patterns differ greatly between males and females. Crossover events occur evenly across the chromosomes in females, but in male meiosis they are restricted to the tip furthest from the centromere of each chromosome, creating very high recombination rates per megabase, similar to the high rates in mammalian sex chromosomes’ pseudo-autosomal regions (PARs). We here used the intronic GC content to indirectly in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…This study also identified a region of high recombination on the end of the Y chromosome opposite to the centromere, consistent with the findings of Lisachov et al (2015). The localization of crossovers in males to the tips of all chromosomes is consistent with the high GC content found there (Charlesworth et al 2020b). Charlesworth et al (2020a) reported a crossover between the X and Y of P. reticulata in a region previously hypothesized to be a nonrecombining stratum.…”
Section: : Introductionsupporting
confidence: 87%
“…This study also identified a region of high recombination on the end of the Y chromosome opposite to the centromere, consistent with the findings of Lisachov et al (2015). The localization of crossovers in males to the tips of all chromosomes is consistent with the high GC content found there (Charlesworth et al 2020b). Charlesworth et al (2020a) reported a crossover between the X and Y of P. reticulata in a region previously hypothesized to be a nonrecombining stratum.…”
Section: : Introductionsupporting
confidence: 87%
“…Based on the total size in the published assembly, plus the two unplaced scaffolds, totalling about 815 kb, that we inferred from the X. maculatus assembly and mapped to the guppy PAR (see above), our results do not change the conclusion that the guppy PAR cannot be larger than a couple of megabases ( Bergero et al 2019 ). Assuming that consistent high intronic high GC content of a region reflects a high recombination rate that causes GC-biased gene conversion (see Charlesworth et al 2020 ), the uniformly high GC content (Supplementary Figure S2) of the scaffold that our map reveals to be terminal ( Figure 4 ) suggests that recombination rates are uniformly high throughout the guppy PAR, rather than being clustered into parts of the PAR with very high crossover rates.…”
Section: Resultsmentioning
confidence: 86%
“…The candidate contig is followed by a GC-rich region, corresponding to the end of the chromosome where recombination is known to be high and shows no evidence for sex-linkage ( Bergero et al. 2019 ; Charlesworth et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%